Going nano with protic ionic liquids—the synthesis of carbon coated Li3V2(PO4)3 nanoparticles encapsulated in a carbon matrix for high power lithium-ion batteries. (March 2015) - Zhang, Xiaofei; Kühnel, Ruben-Simon; Hu, Huating; Eder, Dominik; Balducci, Andrea
Abstract: A solution-chemistry approach was developed to prepare carbon-coated Li3 V2 (PO4 )3 nanoparticles embedded in a micrometer-sized carbon matrix. The material was obtained by a facile one-pot synthesis involving a protic ionic liquid as a soft template and carbon source. To the best of our knowledge, the rate performance of electrodes based on this material is among the highest reported so far for Li3 V2 (PO4 )3 due to the favorable nanoarchitecture combined with high electronic conductivity of the material. The capacity of the electrode only smoothly declines with increasing current density and reaches a value of about 100 mAh g −1 at 100C when cycled between 3.0–4.3 V vs. Li/Li + . Furthermore, excellent capacity retention of 70% after 10, 000 cycles at 50C is demonstrated. Graphical abstract: Highlights: Protic ionic liquids are excellent soft templates. Protic ionic liquid makes possible the formation of nanostructures. Li3 V2 (PO4 )3 nanoparticles encapsulated in a carbon matrix were successfully prepared. An excellent capacity of 100 mAh g − 1 at 100C was obtained for this cathode material.